Effect of Particle Size on the HDS Activity of Molybdenum Sulfide - Carola Contreras; Fernanda Isquierdo; Pedro Pereira-Almao; Carlos E. Scott (Journal of Nanotechnology)
More than half of the total world oil reserves are heavy oil, extra heavy oil, and bitumen; however their catalytic conversion to more valuable products is challenging. The use of submicronic particles or nanoparticles of catalysts suspended in the feedstock may be a viable alternative to the conversion of heavy oils at refinery level or downhole (in situ upgrading). In the present work, molybdenum sulfide (MoS2) particles with varying diameters (10000–10 nm) were prepared using polyvinylpyrrolidone as capping agent. The prepared particles were characterized by DLS, TEM, XRD, and XPS and tested in the hydrodesulfurization (HDS) of a vacuum gas oil (VGO). A correlation between particle size and activity is presented. It was found that particles with diameters around 13 nm show double the HDS activity compared with the material with micrometric particle sizes (diameter ≈ 10,000 nm).